2019
DOI: 10.2147/ijn.s218101
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preparation And Antibacterial Effects Of Carboxymethyl Chitosan-Modified Photo-Responsive <em>Camellia</em> Sapogenin Derivative Cationic Liposomes</p>

Abstract: BackgroundBacterial resistance to antibiotics is a persistent and intractable problem. The sapogenin isolated from the seeds of Camellia oleifera can inhibit antibiotic-resistant bacteria after structural modification.PurposeThis study aims to improve sapogenin's antibacterial activity and avoid bacterial resistance based on nano-preparation with photo responsiveness.MethodsThe liposome shell material of carboxymethyl chitosan-phosphatidyl ethanolamine (CMC-PE) was prepared using amidation reaction, and photo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It has been known that overused antibiotics in animal feed could lead to the development of drug-resistant bacteria and drug residues as threats to human health, so they have been phased out as growth promoters in many countries (12)(13)(14). On the other hand, there is increasing value in finding natural and harmless feed additives to strengthen the immune system and fight against various diseases, thus new antibiotic substitution strategies and alternative feed additives such as microecological preparations and traditional herbal medicine are currently increasing in popularity (15)(16)(17). It reported that the dietary supplementation with propionibacteria promoted mucus secretion characterized by rising goblet cells counts, neutral mucin production, and the longer villus-crypt units.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that overused antibiotics in animal feed could lead to the development of drug-resistant bacteria and drug residues as threats to human health, so they have been phased out as growth promoters in many countries (12)(13)(14). On the other hand, there is increasing value in finding natural and harmless feed additives to strengthen the immune system and fight against various diseases, thus new antibiotic substitution strategies and alternative feed additives such as microecological preparations and traditional herbal medicine are currently increasing in popularity (15)(16)(17). It reported that the dietary supplementation with propionibacteria promoted mucus secretion characterized by rising goblet cells counts, neutral mucin production, and the longer villus-crypt units.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of mPEG-PEI-(NBS, OA) nanomicelles was estimated by MTT viability assay against A549 cells [ 37 ]. Briefly, the A549 cells were seeded in a 96-well plate at a density of 1 × 10 4 cells per well and incubated in DMEM medium at 37 °C in the presence of 5% CO 2 for 24 h. After removing the culture medium, the cells were treated with 100 μL of fresh medium containing different concentrations of the nanomicelles (the corresponding concentration was 0.5, 1, 2, 4, 8, 16, 32, 64, 128, and 256 μg/mL) for 24 h. Subsequently, the medium containing the nanomicelles was removed, and the cells were washed three times with PBS solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, because bacteria have difficulty surviving from physically destroyed cell structures, cationic liposomes can also destroy bacterial membranes and walls through electrostatic interactions, so cationic liposomes have specific antibacterial mechanisms and antibacterial activity, and this specific mechanism also effectively reduces the risk of enhanced bacterial resistance (Zhang et al, 2019). Cationic liposomes, such as those composed of dioctyl-dimethylammonium bromide (DODAB), are inherently inhibitory to both gram-Frontiers in Bioengineering and Biotechnology frontiersin.org negative and gram-positive bacteria, even without encapsulated antibiotics (Laune et al, 2022).…”
Section: Other Nanomaterialsmentioning
confidence: 99%